ANALISIS STRUKTUR RETORIKA PROBLEM JUSTIFYING PROJECT PADA TEKS PENDAHULUAN ARTIKEL JURNAL BIDANG PENELITIAN TINDAKAN KELAS - Sasih Karnita Arafatun (UNMUHBABEL Press, 2019)
The goal of this study is to find out rhetoric structure in introduction text journal articles research class action with ideal according structure model of PJP rethoric. This research is using a descriptive method. The data of this study is the author's speech in part of introduce journal artcle